Penguatan literasi keuangan siswa SMK Darun Najah Kapedi Bluto Sumenep - Utama, Joni Alif; Fitriyah, Rizka; Arifqi, Moh. Musfiq (Nur Science Institute, 2025)
Financial literacy is a fundamental competency that young generations must possess in order to face economic challenges in the digital era. This community service program aims to strengthen the financial literacy awareness of students at SMK Darun Najah Kapedi Bluto Sumenep as a strategy to foster financially intelligent generations and promote economic independence through the principle of saving. The program employed the ADIED approach (Analysis, Design, Implementation, Evaluation, and Development). The activities included focus group discussions (FGD), financial literacy training, mentoring, and evaluation based on pretest and posttest assessments. The evaluation results demonstrated a significant improvement in students’ understanding, with an N-Gain score of 0.72 (high category). These findings indicate that thematic-based learning is effective in enhancing students’ awareness of the importance of financial planning, risk management, and prudent economic decision-making.